2012
DOI: 10.1093/aob/mcs198
|View full text |Cite
|
Sign up to set email alerts
|

Seed storage at elevated partial pressure of oxygen, a fast method for analysing seed ageing under dry conditions

Abstract: Background and AimsDespite differences in physiology between dry and relative moist seeds, seed ageing tests most often use a temperature and seed moisture level that are higher than during dry storage used in commercial practice and gene banks. This study aimed to test whether seed ageing under dry conditions can be accelerated by storing under high-pressure oxygen.MethodsDry barley (Hordeum vulgare), cabbage (Brassica oleracea), lettuce (Lactuca sativa) and soybean (Glycine max) seeds were stored between 2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
133
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(138 citation statements)
references
References 47 publications
1
133
1
3
Order By: Relevance
“…Studies carried out using dry seeds have reported either neutral or positive effects of anoxic storage on seed longevity (Gane, 1948;Roberts and Abdalla, 1968;Shejbal, 1979;Bennici et al, 1984;Shrestha et al, 1985;Barzali et al, 2005;González-Benito et al, 2011;Schwember and Bradford, 2011). The positive correlation between the oxygen level in the storage environment and the level of seed deterioration has also been shown in experiments in which an elevated oxygen concentration was created by hyperbaric storage (Ehrenberg et al, 1957;Kronstad et al, 1959;MoutschenDahmen et al, 1959;Groot et al, 2012).…”
Section: Anoxia and Seed Viabilitymentioning
confidence: 95%
“…Studies carried out using dry seeds have reported either neutral or positive effects of anoxic storage on seed longevity (Gane, 1948;Roberts and Abdalla, 1968;Shejbal, 1979;Bennici et al, 1984;Shrestha et al, 1985;Barzali et al, 2005;González-Benito et al, 2011;Schwember and Bradford, 2011). The positive correlation between the oxygen level in the storage environment and the level of seed deterioration has also been shown in experiments in which an elevated oxygen concentration was created by hyperbaric storage (Ehrenberg et al, 1957;Kronstad et al, 1959;MoutschenDahmen et al, 1959;Groot et al, 2012).…”
Section: Anoxia and Seed Viabilitymentioning
confidence: 95%
“…High ROS concentration leads to damaging oxidation of vital cell materials in seeds, including proteins, DNA, RNA, and cell membrane lipids, and decreasing cell integrity. ROS cause lipid peroxidation and degradation of polyunsaturated fatty acids, producing malondialdehyde (Rajjou et al, ; Rajjou & Debeaujon, ), that ultimately causes disintegration of the seed structure and reduces seed longevity (Groot et al, ).…”
Section: Physiological and Genetic Factors Are Involved In Seed Longementioning
confidence: 99%
“…• Larger seed size partially offset reductions in germination and the seedling vigor index, especially in high sodic salt stress conditions. S eed germination is influenced by both seed age and size (Groot et al, 2012;Kos and Poschlod, 2010). The seed ageing process increases water and gas permeability via seed coat permeability changes and thereby influences seed germination.…”
Section: Core Ideasmentioning
confidence: 99%
“…S eed germination is influenced by both seed age and size (Groot et al, 2012; Kos and Poschlod, 2010). The seed ageing process increases water and gas permeability via seed coat permeability changes and thereby influences seed germination.…”
mentioning
confidence: 99%